Step-by-step explanation:
General equation of circle:
(x - a)² + (y - b)² = r².
Therefore we have x² + (y - 3.5)² = 12.25.
Answer:
Given f(x) and g(x), please find (fog)(X) and (gof)(x) f(x) = 2x g(x) = x+3
Given f(x) and g(x), please find (fog)(X) and (gof)(x)
f(x) = 2x g(x) = x+3
print Print document PDF list Cite
Quick Answer
(fog)(x) = 2x + 6
(gof)(x) = 2x + 3
Expert Answers
HALA718 eNotes educator| CERTIFIED EDUCATOR
f(x) = 2x
g(x) = x + 3
First let us find (fog)(x)
(fog)(x) = f(g(x)
= f(x+3)
= 2(x+3)
= 2x + 6
==> (fog)(x) = 2x + 6
Now let us find (gof)(x):
(gof)(x) = g(f(x)
= g(2x)
= 2x + 3
==> (gof)(x) = 2x + 3
Step-by-step explanation:
Answer: 37 fruit pies+42 fruit juices=79 total items
(a) 37*1.65= $61.05
42*1.36= $57.12
(b) Mr Sanchez's class earned more money.
(c) Mr. Sanchez's class earned $3.93 more than Mr. Kelly's class
$61.05-$57.12= $3.93
Step-by-step explanation: